A Case of 'Camouflaged Insulinoma & Diazoxide Quandary - Dr Sonam Tshering,; Dr Saquib Navid Siddiqui,; Dr Irfan Khan, (International Journal of Innovative Research in Medical Science, 2021)
Insulinomas are rare cause of neuroendocrine tumour which secretes insulin leading to hyperinsulinism. Diagnosis requires biochemical evaluation followed by tumour localization. We report a case of an adult women, who, had multiple admissions with dizziness, funny turns and double vision for at least 2 years and seen by the multiple medical specialties before the diagnosis of Insulinoma was made. Endoscopic Ultrasound finally localized the tumour despite negative results on multiple non-invasive imaging modalities. Prior to the localization of tumour, she was treated with dietary modifications followed by Diazoxide, which, she had to abandon due to refractory fluid overload as a result of it. A trial of SC Octreotide was started with excellent results whilst waiting for surgery. She underwent laparoscopic distal pancreatectomy on 22/02/2019.